Fenomenologi : Caring Perawat Terhadap Klien Dengan Kondisi Kritis Di Instalasi Gawat Darurat – Rumah Sakit Dr. Saiful Anwar Malang - Janes Jainurakhma; Indah Winarni; Setyoadi Setyoadi (coba, 2013)
Caring is an important part of nursing process that difficult to be apart. Emergency nursing is a profession that required health care providers with fast performance, accurate, and quality of complicated and holistic problems. A lot of patients with critical condition at emergency department, they ask a quality of nursing services and it is affected by the quality of a nurse caring. Without caring passion, a nurse vulnerable to act that violate ethical of nursing, no exception nursing profession at emergency installations of RSSA Malang. The purpose of this study is to explore the experience of nurse caring for clients with critical condition at emergency installations of RSSA Malang. This study used a qualitative approach, with interpretive phenomenological method. Purposive sampling is a method used in this study, the criteria of experience as nurse in the emergency installations of RSSA Malang at least 5 years, still working in the emergency installations of RSSA Malang, and willing as participant. Using semi-structure interviews technique, and analyzed by Miles and Huberman model approach. The results led to three themes, namely: the resque of critically ill patients, improve patient and family confidence, desire to do the best for crical patients. Based on the results of the study are expected to follow up with the theme of the next study of emergency nurses caring of the perpective of patient and families, and needs to be improved further for the training of emergency skill of nurses in the emergency department, so thet skills and knowledge of nurses in handling critical patients better. Key words: caring, nursing experience, critical patient.